SISTEM MONITORING DAN KONTROL MOUSETRAP DENGAN FEEDER OTOMATIS BERBASIS MOBILE ANDROID - Rendy fajar bakti; Pressa Perdana Surya; Rini Puji Astutik (Politeknik Harapan Bersama Tegal, 2022)
The rapid development of technology, especially in the field of electronics, can be utilized optimally so that every human job becomes easier. One of them is an automatic mouse trap based on the Internet of Things (IoT) to reduce the rat population in residential areas, storage warehouses and agricultural land. The development of rat trapping tools from conventional to semi-automatic aims to make it easier to check and control so that this tool can be optimized. work according to its function without endangering the people around. This study aims to try to develop a mousetrap device by utilizing technology that is developing very fast today.By utilizing the NodeMCU Esp 8266 microcontroller as the main control to run several controllers, namely the ultrasonic sensor which is used as a receptionist which then learns with the NodeMCU to display applications and several components that work according to the previously created program, the advantages of developing this tool can make it easier for users because can save energy and time and the user does not need to check the trap to the location where the tool is installed, the trap can be monitored and controlled using the application as long as it is connected to the internet network.